High vs. Low Radiation Dose of Concurrent Chemoradiotherapy for Esophageal Carcinoma With Modern Radiotherapy Techniques: A Meta-Analysis - Sun, Xin; Wang, Lei; Wang, Yang; Kang, Jingjing; Jiang, Wei; Men, Yu; Hui, Zhouguang (Frontiers in Oncology, 2020)
Purpose: The aim of this study was to evaluate the clinical benefit of different radiation doses in concurrent chemoradiotherapy (CCRT) for esophageal carcinoma using modern radiotherapy techniques. Methods: A systematic review was conducted by screening PubMed, EMBASE, Cochrane Central Register of Controlled Trials, SCOPUS, Wanfang and Chinese National Knowledge Infrastructure (CNKI) databases with prespecified searching strategy. Studies which compared high radiation dose group with low dose radiation group using modern radiotherapy techniques for esophageal cancer patients in CCRT were identified. The hazard ratios (HR) for overall survival (OS) and the odds ratios (OR) for local-regional failure (LRF), distant metastasis (DM) and toxicities were considered as the outcomes of interest. R 3.6.2 software was used for statistical analysis. Results: Twelve studies involving 10896 patients were included for analyses. The results showed that high dose group had better OS (HR=0.79, 95%CI=0.70-0.90, P=0.0004) and the local-regional control (OR=0.59, 95% CI=0.46-0.76, P<0.0001), especially for patients who diagnosed with squamous cell carcinoma (SCC). The subgroup analyses further indicated that ≥ circa 60Gy can significantly improve the OS (HR=0.73, 95%CI=0.68-0.80, P<0.0001) as well as the local-regional control (OR=0.54, 95% CI=0.40-0.74, P<0.0001) as compared with < circa 60Gy. Another subgroup analysis comparing ≤ 50.4Gy with > 50.4Gy showed no substantial difference in OS (HR=0.98, 95% CI=0.93-1.03, P=0.43). In addition, there is no significant differences between the two groups in grade 3-5 radiation pneumonitis (OR=1.05, 95% CI=0.54-2.05, P=0.89), grade 3-5 radiation esophagitis (OR=1.40, 95% CI=0.93–2.11, P=0.11), treatment-related death (OR=1.60, 95% CI=0.70-3.66, P=0.27), and DM (OR=1.21, 95% CI=0.92-1.59, P=0.17). Conclusions: For esophageal carcinoma receiving CCRT with modern radiation techniques, evidence suggested that high dose radiotherapy, especially ≥ circa 60Gy, had potentials to improve the OS and local-regional control without increase of severe toxicities when compared with low dose radiotherapy. The result needs to be confirmed by randomized clinical trials.